Space Weather Modeling Capabilities Assessment: Auroral Precipitation and High‐Latitude Ionospheric Electrodynamics. Issue 2 (5th February 2019) - Robinson, Robert; Zhang, Yongliang; Garcia‐Sage, Katherine; Fang, Xiaohua; Verkhoglyadova, Olga P.; Ngwira, Chigomezyo; Bingham, Suzy; Kosar, Burcu; Zheng, Yihua; Kaeppler, Stephen; Liemohn, Michael; Weygand, James B.; et al.
Abstract: As part of its International Capabilities Assessment effort, the Community Coordinated Modeling Center initiated several working teams, one of which is focused on the validation of models and methods for determining auroral electrodynamic parameters, including particle precipitation, conductivities, electric fields, neutral density and winds, currents, Joule heating, auroral boundaries, and ion outflow. Auroral electrodynamic properties are needed as input to space weather models, to test and validate the accuracy of physical models, and to provide needed information for space weather customers and researchers. The working team developed a process for validating auroral electrodynamic quantities that begins with the selection of a set of events, followed by construction of ground truth databases using all available data and assimilative data analysis techniques. Using optimized, predefined metrics, the ground truth data for selected events can be used to assess model performance and improvement over time. The availability of global observations and sophisticated data assimilation techniques provides the means to create accurate ground truth databases routinely and accurately. Key Points: A working team has been established to develop a process for validation of auroral precipitation and electrodynamics models Validation of auroral electrodynamic parameters requires generation of ground truth data sets for selected events Current observations and data assimilation techniques continue to improve the accuracy of global auroral electrodynamic specification